Braided Creek a conversation in poetry - Kooser, Ted 1939-; Harrison, Jim 1937-2016 (Copper Canyon Press, 2023)
"An expanded anniversary edition of a collection of poems by Ted Kooser and Jim Harrison."
Keywords: American poetry / 20th century; Poésie américaine / 20e siècle; poetry; Poésie; Anthologie